THE INFLUENCE AND DYNAMICS OF ISLAMIC CIVILIZATION IN THE INDONESIAN ARCHIPELAGO - Wijaya Wijaya (Journal of Noesantara Islamic Studies, 2026)
This study examines the dynamics and civilization of Islam in the Indonesian archipelago, focusing on intercultural interactions that shaped the region's social and cultural structures. Islam, which arrived through trade and da'wah (Islamic preaching), played a significant role in shaping civilization in the Indonesian archipelago through the exchange of knowledge and technology, as well as the adaptation of local cultures. The significant contributions of Muslim scholars in mathematics, medicine, and philosophy also influenced the development of science in the Indonesian archipelago. Meanwhile, cultural interactions between Islam and local cultures resulted in acculturation that enriched the Indonesian archipelago's artistic and cultural heritage, such as performing arts and gamelan music. This study uses a qualitative approach using literature study methods and historical analysis to explore how Islamic civilization adapted and developed in the Indonesian archipelago, as well as how it influenced local social, legal, and cultural structures. In conclusion, Islamic civilization in the Indonesian archipelago was not limited to religious aspects but also encompassed the interconnected social, economic, and cultural spheres that shaped the identity of the Indonesian Muslim community.